Phase I trial comparing bile acid and short-chain fatty acid alterations in stool collected from human subjects treated with omadacycline or vancomycin - Jo, Jinhee; Hu, Chenlin; Horvath, Thomas D.; Haidacher, Sigmund J.; Begum, Khurshida; Alam, M. Jahangir; Garey, Kevin W. (Antimicrobial agents and chemotherapy, 2025)
Omadacycline, an aminomethylcycline tetracycline, has a low propensity to cause infection (CDI) in clinical trials. Omadacycline exhibited a reduced bactericidal effect compared with vancomycin on key microorganisms implicated in bile acid homeostasis and short-chain fatty acids (SCFAs), key components of CDI pathogenesis. The purpose of this study was to assess bile acid and SCFA changes in stool samples from healthy volunteers given omadacycline or vancomycin. Stool samples were collected daily from 16 healthy volunteers, who were given oral omadacycline or vancomycin for 10 days. Daily stool samples were assessed for bile acids and SCFA concentrations using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Bile acids changed significantly over time for all subjects ( < 0.01 for each bile acid), with vancomycin causing a larger change in the primary bile acids, cholic acid ( < 0.001) and chenodeoxycholic acid ( < 0.001), and a reduced change in the secondary bile acid, lithocholic acid ( < 0.001). The secondary bile acid ursodeoxycholic acid was reduced less by vancomycin than by omadacycline ( < 0.001). All SCFA concentrations were reduced from baseline with a larger effect observed with vancomycin for isobutyric acid ( = 0.0034), propionic acid ( = 0.0012), and acetic acid ( = 0.047). Microbial changes associated with the use of vancomycin versus omadacycline were also associated with changes in bile acid homeostasis and SCFA concentrations. Oral omadacycline produced a distinctive metabolomic profile compared with vancomycin when administered to healthy subjects. The metabolic findings help further our understanding of the lower CDI risk properties of omadacycline and warrant phase 2 investigations using omadacycline as a CDI antibiotic. The purpose of this study was to assess bile acid and SCFA changes in stool samples obtained from healthy volunteers given omadacycline or vancomycin. Stool samples were collected daily from 16 healthy volunteers given a 10-day oral course of omadacycline or vancomycin. Vancomycin caused a larger change in the primary bile acids and SCFA concentrations compared with omadacycline. The metabolic findings help further our understanding of the mechanistic basis for the lower-risk properties of omadacycline causing CDI and warrant phase 2 investigations using omadacycline as a CDI antibiotic. This study is registered with ClinicalTrials.gov as NCT06030219.